Referendum opposition to fluoridation and health literacy: a cross-sectional analysis conducted in three large US cities. Issue 2 (1st February 2019) - Curiel, John A; Slade, Gary D; Christian, Thu-Mai L; Lafferty-Hess, Sophia; Carsey, Thomas M; Sanders, Anne E
Abstract : Objective: To explore health literacy as a marker of voter confusion in order to understand the basis for public opposition to community water fluoridation. Design: A cross-sectional study. Setting: Conducted in three large US cities of San Antonio, Texas (602 voting precincts); Wichita, Kansas (171 voting precincts); and Portland, Oregon (132 voting precincts). Precinct-level voting data were compiled from community water fluoridation referendums conducted in San Antonio in 2002, Wichita in 2012 and Portland in 2013. Participants: Voter turnout expressed as a percentage of registered voters was 38% in San Antonio (n=2 92 811), 47% in Wichita (n=129 199) and 38% in Portland (n=164 301). Main outcome measures: The dependent variable was the percentage of votes in favour of fluoridating drinking water. Precinct-level voting data were mapped to precinct scores of health literacy, and to US Census and American Community Survey characteristics of race/ethnicity, age, income and educational attainment. Multilevel regression with post-stratification predicted the precinct mean health literacy scores, with weights generated from the National Association of Adult Literacy health literacy survey, with item response theory computed scoring for health literacy. Predictive models on voter support of community water fluoridation were compared using robust linear regression to determine how precinct-level characteristics influenced voter support in order to determine whether health literacy explained more variance in voting preference than sociodemographic characteristics. Results: Precinct-level health literacy was positively associated with voter turnout, although sociodemographic characteristics were better predictors of turnout. Approximately 60% of voters opposed community water fluoridation in Wichita and Portland, whereas in San Antonio, a small majority (53%) voted in favour of it. Models suggest that a one SD increase in health literacy scores predicted a 12 percentage point increase support for community water fluoridation. Conclusion: Educational attainment and health literacy are modifiable characteristics associated with voting precincts' support for community water fluoridation.